ELEMENTS AND FUNCTIONS OF MECHANISM FOR INNOVATION ENVIRONMENT FORMATION UNDER REGIONAL CONDITIONS - Novoselov S.V.; Mayurnikova L.A.; Kilina I.A. (Техника и технология пищевых производств)
An important success factor for innovative activity of countries, industries, firms is the availability of qualified personnel. A very small number of educational institutions train highly qualified personnel for innovative business in Russia. At the same time the range of non-governmental institutions offering courses in the fields which are components of innovation, such as marketing, economics, etc. promote poor training. To correct the situation one should create high demand for knowledge. The consumers, i.e. innovative entrepreneurship, including small enterprising are in need of development. An effective solution of this problem may be based on the formation and development of innovation environment and innovation sphere in different areas of social life. The basis for modeling the development process of food service establishments based on the development and implementation of innovative projects under regional conditions are presented. The concepts of innovation environment and innovation sphere are given. The main elements of mechanism for formation of the innovation environment and its functions promoting the efficiency of innovative activities and implementing innovative projects are described. Selection of elements is based on the patterns of the innovation cycle which results in options depending on the kind of innovative activity under regional and field of industry conditions. The described functions of the main elements of the mechanism for innovation environment formation make it possible to determine the variant approaches to the innovative activity management based on knowledge management. It is shown that the overall innovation environment promotes the activation of scientific-innovative activity and, as a consequence, the development of enterprises and organizations on the basis of innovative projects and programs.